Associations between self-reported sleep duration and incident cardiovascular diseases in a nationwide prospective cohort study of Chinese middle-aged and older adults - Zhao, Qing; Zhu, Yuan; Zhang, Yu; Luo, Huanyuan; Ma, Yantao; Chen, Xiaoshan; Gu, Jiaming; Wang, Lizhi (Frontiers in Cardiovascular Medicine, 2024)
PurposeThis study explores the correlation between sleep duration and cardiovascular disease (CVD) among middle-aged and older adults in China. Furthermore, we aim to investigate the association between sleep duration and incident CVD in this population, while assessing potential variations across different age and gender subgroups.MethodsUtilizing data from the nationwide prospective survey of the China Health and Retirement Longitudinal Study (CHARLS) conducted in 2011, 2013, 2015, and 2018, involving 17,596 participants aged 45 years and above, we employed Cox proportional hazards regression models. These models were used to examine the impact of baseline sleep duration on CVD, considering age (middle-aged/elderly) and gender (male/female) groups.ResultsOver the 8-year follow-up, 2,359 CVD events were recorded. Compared to individuals sleeping 6–8 h per day, a short sleep duration (≤6 h/day) was significantly associated with an increased risk of CVD (HR: 1.17, 95% CI: 1.03–1.33). Subgroup analysis revealed a more pronounced relationship in participants aged ≥60 years, where both short sleep duration (≤6 h/day) (HR: 1.17, 95% CI: 1.02–1.35) and long sleep duration (>8 h/day) (HR: 1.20, 95% CI: 1.02–1.41) were significantly associated with an elevated risk of CVD. Specifically, among female participants, short sleep durations (≤6 h/day) was significantly associated with CVD (HR: 1.24, 95% CI: 1.05–1.47).ConclusionShort sleep durations can serve as predictive factors for CVD in China's population aged 45 and above, particularly among elderly female participants. Our study underscores the importance of considering sleep health as a critical aspect when formulating strategies for enhancing CVD prevention.